Using an Integrated Model of Strain and Routine Activities to Explore the Reciprocal Relationship Between Direct/Various Victimization and Criminal Coping Among Serious Adolescent Offenders - Park, Yeoju (Crime & delinquency, 2022)
Using an integrated model of general strain and lifestyle/routine activities theories, the study aimed to prospectively assess the reciprocal relationship between direct victimization, vicarious victimization, and delinquency/crime over time among serious offenders. A cross-lagged path model was conducted using three waves from the Pathways to Desistance Study. Past victimization consistently predicted future victimization, while past delinquency/crime consistently affected future delinquency/crime, demonstrating stability across these variables. Prior vicarious victimization also indirectly increased subsequent direct victimization and delinquency/crime. However, there were no direct or indirect effects found between direction victimization and later vicarious victimization or delinquency/crime, or between delinquency/crime and later direct or vicarious victimization. Sensitivity analyses revealed the contemporaneous effects of victimization were more consequential on offending than the lagged effects.